Performance, Monitoring, and Evaluation in China - Wong, Christine (World Bank, Washington, DC, 2014)
Amidst all the hoopla about China's rise, it is useful to remember that China is a developing country whose transition to a market economy is not yet complete, with institution building still underway. The uneven pace of progress is reflected in the state of its public sector, but in some respects, China s public sector looks formidable. Most often mentioned is the government s treasure chest of US$3 trillion in foreign reserves. Even more enviable, government revenues have grown at annual rates of over 20 percent for a decade (China statistics 2011), fuelling a steep fiscal expansion at a time when so many countries are being forced to undergo painful consolidations. The government s reputation was further burnished in the post-Lehman global financial crisis, when, after a brief, though sharp, downturn in 2008, China became the first major economy to return to robust growth, propelled by a stimulus program that was, in relative terms, by far the biggest in the world. The bold stimulus and quick economic recovery seemed to show off an effective public sector able to implement national policies swiftly.